Systematic Scoping Literature Review of Disparities in Stage of Endometrial Cancer [A321]. (May 2022) - Najor, Anna; Melson, Valerie; Lyu, Junrui; Bakkum-Gamez, Jamie; Sherman, Mark E.; Destephano, Christopher
Abstract : INTRODUCTION: Endometrial cancer (EC) in the United States is twice as lethal for Black than White people with a uterus (PWU), partly due to disparities in stage at diagnosis. This systematic scoping review utilizes the Pathway to Treatment framework to identify actionable care and evidence gaps. METHODS: The complete protocol was previously published (DOI 10.1186/s13643-021-01649-x). Structured searches of PubMed, EMBASE, Scopus, and Cochrane Central Register of Controlled Trials were performed. Two reviewers screened abstracts and then full articles for eligibility. Data meeting quality criteria were qualitatively synthesized. RESULTS: Out of 2, 171 records, 24 were included, with 9 reporting on appraisal, 4 on help seeking, 5 on diagnostic, and 10 on pre-treatment intervals. Study quality ratings were heterogenous, between 3 and 9 per Newcastle-Ottawa, with a median score of 7.0. Based on 2, 059 PWU from four studies, no disparities in EC-relevant health literacy were identified. Based on 2, 991 PWU from one study, willingness of Black PWU to seek care for EC symptoms was either the same or greater than White PWU. Based on 3, 006 PWU from two studies, the physician not disclosing concern for cancer may prolong the diagnostic interval. Based on 743, 139 PWU from five studies, the pre-treatment interval is significantly (all P values<.05) longer for Black and Hispanic PWU, those with less insurance coverage, and those with lower socioeconomic status. CONCLUSION: The Pathway to Treatment framework operationalized the evidence, revealing when disparities in timeliness occur. Interventions to reduce delays in the diagnostic and pre-treatment Intervals are particularly promising for addressing EC stage disparities.